Interfacial nanostructure of solvate ionic liquids and ionic liquid solutions - Coles, S (2018)
The technology employed by human beings for the generation, storage and usage of energy is presently undergoing the fastest and most profound change since the industrial revolution. The changes in the generation and usage of energy necessitate the development of new methods of energy storage. In these systems, electrochemical energy storage will play a crucial role and to this end new electrolytes need to be explored to complement these changes. One such class of liquids is ionic liquids, a class of salts that are molten at room temperature. These liquids have a broad applicability to batteries and supercapacitors. This thesis details work where molecular dynamics simulations have been used to explore the nanostructure of ionic liquids and their mixtures with various molecular solvents at simplistic electrodes. The thesis has two broad sections. The first is covered in Chapter 3, and explores the nanostructure of ionic liquid propylene carbonate solutions, developing a framework through which these nanostructures can be understood. The section concludes that the increasing dilution of ionic liquids decreases the surface charge at which the characteristic ionic liquid oscillatory interfacial structure gives way to a different structure featuring monotonic charge decay. The behaviour of ionic liquids at interfaces is found to be correlated to ion size and type, as well as concentration. A wide divergence in the observed behaviour is shown at positive and negative electrodes due to the asymmetry of propylene carbonate. The second section, consisting of two chapters, explores the interfacial nanostructure of solvate ionic liquids using two different boundary conditions to model the electrode. This work is the first simulation of solvate ionic liquids at electrified interfaces. This section will explore the effect of electrode model on the behaviour of these ionic liquids at the electrode. Chapter 4 uses a fixed charge electrode, whereas Chapter 5 uses one with a fixed potential. The section concludes that regardless of electrode model, the idealised portrait of a solvate ionic liquid - one where the liquid behaves exactly as an aprotic ionic liquid - is not applicable. In Chapter 4's exploration of fixed charged electrodes, the formation of 2 glyme to lithium complexes contradicts the idealised portrait of the liquid. A different change is observed in Chapter 5's exploration of fixed potential electrodes, with both lithium glyme and lithium anion clusters forming at the interface. The key difference between the two studies is that lithium does not coordinate to the electrode in the fixed charge simulations, while in the fixed potential case it does. At the end of Chapter 5 the results are compared against experimental data, with the efficacy of the two models discussed. The aim of both studies is to look at the nanostructure of ionic liquids, when the symmetry between co-ion and cation repulsion - and related effects - is broken by the presence of a non ionic constituent in the liquid.